Letter from Carl D. Duncan to Patricia Whiting, May 3, 1965 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan expresses his frustration regarding stressful aspects of his life and his upcoming retirement, including pressure to sell his home in Menlo Park and being excluded from faculty conferences. Duncan repeatedly mentions his wish to stay an active and inspiring presence on the San Jose College campus.